O conceito de simpatia e o seu papel na filosofia moral de David Hume - Nascimento, Marcos Antonio Alves do (2017)
This dissertation has the objective to investigate the moral’s theory of the scottish philosopher David Hume, concerning with the concept of sympathy and what is its function in the humean moral’s philosophy. It analyzes as well the concept of utilitarianism that according to Hume it must be understood like a general criterion of morality, therefore, all human being has a strong link with society and perceives it like a well-being state of humanity. To fulfil the proposed objective, this research was divided into three chapters. In the first one, I present the general aspects of Hume’s philosophy like empiricism, impressions and ideas, causality, freedom and necessity. In the second chapter, I treat the moral and its distintions, if it has its foundation in the reason or in the sensibility, justice like artificial virtue and the passions. Finally, in the third and last chapter, I treat the sympathy and the utilitarianism, and what its relation with the humean moral.